Exploring socio-contextual factors associated with male smoker's intention to quit smoking - Minsoo Jung (BMC, 2016)
Abstract Background Programs to encourage smokers to quit smoking tobacco have been implemented worldwide and are generally viewed as an effective public health intervention program. However, few studies have examined the social factors that influence a smoker's intention to quit smoking. This study investigated the socio-contextual factors that are associated with the intention to quit smoking among male smokers in South Korea. Methods Data were obtained from a 2014 nationally representative panel that examined the influences of mass media on the health of the Korean population. Members of this panel were recruited using a mixed-method sampling and a combination of random digit dial and address-based sampling designs. Survey questions were based on those used in previous studies that assessed the effects of social context, including mass media and social capital, on health. Multivariate logistic regression analyses of the answers of 313 male smokers were undertaken. Results Male smokers who participated in community-based activities were 2.45 times more likely to intend to quit smoking compared to male smokers in general (95 % confidence interval [CI]: 1.25-6.82). In addition, male smokers who participated in informal social gathering networks were 2.38 times more likely to intend to quit smoking compared to male smokers in general (95 % CI: 1.11-5.10). Moreover, male smokers with high smartphone use were 1.93 times more likely than smokers with low smartphone use to intend to quit smoking within one year (95 % CI: 1.07-3.46). Conclusions A supportive environment that enables male smokers to access beneficial health information and that encourages them to quit smoking is necessary for a stop-smoking program to be effective. The result of this study contribute to establishing a new smoking control policy by identifying socio-contextual factors related to the intention to quit smoking.